Post-Harvest Deterioration of Cassava and its Control Using Extracts of Azadirachta Indica and Aframomum Melegueta - R. N. Okigbo; Ramesh Putheti; C. T. Achusi (E-Journal of Chemistry)
Post-harvest deterioration is the most important cause of loss in cassava production and this is mainly as a result of microbial invasion of the tubers. This research was therefore carried out to identify and control the organisms responsible for post-harvest deterioration of cassava tubers. Ethanolic and water extractions of Azadirachta Indica (A. Juss) leaves and Aframomum melegueta (Schumann) seeds were used as antifungal agents and the susceptibility of four of the isolated pathogenic fungi to them was observed in culture. The tested organisms were Aspergillus niger Van Tiegh, Botryodiplodia theobromae Pat, Fusarium solani (Mart). Sacc and Penicillium oxalicum Currie and Thom. All tested organisms showed different degrees of inhibitions by the extracts with A. niger being the most inhibited by ethanolic extraction of A. melegueta. The overall result showed that A. indica was more active on the organisms though it’s effects and that of A. melegueta were not significantly different (P>0.05).